2008
DOI: 10.1021/tx700349r
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Is the Main Nucleophilic Target of Human Plasma: A Protective Role Against Pro-atherogenic Electrophilic Reactive Carbonyl Species?

Abstract: The aim of this work was to study the metabolic fate of 4-hydroxy- trans-2-nonenal (HNE) in human plasma, which represents the main vascular site of reactive carbonyl species (RCS) formation and where the main pro-atherogenic target proteins are formed. When HNE was spiked in human plasma, it rapidly disappeared (within 40 s) and no phase I metabolites were detected, suggesting that the main fate of HNE is due to an adduction mechanism. HNE consumption was then monitored in two plasma fractions: low molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 61 publications
3
105
0
1
Order By: Relevance
“…8B). Physiological processes such as the regulation of vascular homeostasis, oxidative stress, and lipid peroxidation generate a wide range of small electrophiles that react with HSA-Cys 34 , including nitric oxide, small aldehydes, and oxygen radicals (18,30,31). Because the thiol of HSA-Cys 34 resides inside a 10 Å crevice in the HSA molecule (32,33), the preponderance of small added masses in our sample may also reflect steric restriction of bulky molecules from the reaction site.…”
Section: Fs-srm Of T3 Adducts From Human Samples-followingmentioning
confidence: 96%
See 1 more Smart Citation
“…8B). Physiological processes such as the regulation of vascular homeostasis, oxidative stress, and lipid peroxidation generate a wide range of small electrophiles that react with HSA-Cys 34 , including nitric oxide, small aldehydes, and oxygen radicals (18,30,31). Because the thiol of HSA-Cys 34 resides inside a 10 Å crevice in the HSA molecule (32,33), the preponderance of small added masses in our sample may also reflect steric restriction of bulky molecules from the reaction site.…”
Section: Fs-srm Of T3 Adducts From Human Samples-followingmentioning
confidence: 96%
“…Because we had previously observed that specific xenobiotic adducts of HSA-Cys 34 were present at much higher concentrations than those of Hb-Cys 93␤ in human blood (14 -16), we chose HSA-Cys 34 for profiling experiments. In fact, HSA-Cys 34 is a well known scavenger of small electrophiles that accounts for about 80% of all free thiols in human serum (17,18), and HSA-Cys 34 adducts have been unambiguously detected from reactions with aldehydes, nitrogen mustards, oxiranes, quinones, metal ions, and a host of drugs [reviewed in (7)]. Following tryptic digestion of HSA, all thiol adducts should be bound to a single peptide, which we designate as T3 (the third largest tryptic peptide of HSA), with sequence ALVLIAFAQYLQQC 34 PFEDHVK and an average mass of 2433.87 Da.…”
mentioning
confidence: 99%
“…On the basis of these findings, we proposed [59] a new MS approach, based on LC-MS/MS analysis of tag HNE/ACR-modified peptides of carbonylated albumin and actin that can be applied to the digested proteins isolated from the biological samples or directly to the digested sample (one-shot procedure). By using 2-D SDS-PAGE followed by immunoblot analysis and MALDI-TOF mass fingerprint analysis of the isolated and digested protein, we demonstrated that HSA is the major nucleophilic plasma target of HNE [60] and that Cys 34 is the target site on HSA for a,b-unsaturated aldehydes adduction.…”
Section: In Vitro Evidencementioning
confidence: 98%
“…We have previously found that free plasma RCSs rapidly disappear (by almost 70% within 5 min) during reperfusion, since they form covalent adducts with plasma proteins [22]. By proteomic studies, we identified albumin as their main protein target and Cys34 as the most reactive site, whose high nucleophilic reactivity has been clarified by molecular modeling studies [35]. Based on these results, we aimed at identifying the chemical structures of RCSs adducted to Cys34.…”
Section: Discussionmentioning
confidence: 97%